Improving on-farm agricultural water productivity in the Karkheh River Basin - Oweis, Theib Y.; Siadat, H.; Abbasi, F. (CGIAR Challenge Program on Water and Food, 2009)
Improving On-farm Agricultural Water Productivity in the Karkheh River Basin (KRB) was a CPWF project that aimed at enhancement of agricultural water productivity (WP) under irrigated and rainfed conditions in Karkheh River Basin. It was launched in Iran through the partnership of ICARDA and the Iranian NARES under the Agricultural Extension, Education, and Research Organization. The project lasted for more than four years between 2004 and 2008. Whereas capacity building was an important part of the agenda, PN8 was a participatory, multi-disciplinary, and action-oriented project that carried out mostly on-farm trials. Findings included existing crop water productivity, suitable technologies for their improvement, interactions between the upper and lower KRB, and a review of the prevailing water policies and institutions